Acute and long‐term success of left atrial anterior line and mitral isthmus line ablation in patients after mitral valve surgery. Issue 9 (16th August 2022) - Bertels, Jana; Rottner, Laura; Heeger, Christian‐Hendrik; Maurer, Tilman; Reissmann, Bruno; Ouyang, Feifan; Mathew, Shibu; Wohlmuth, Peter; Schlüter, Michael; Kuck, Karl‐Heinz; Metzner, Andreas; Lemeš, Christine
Abstract: Background: Perimitral flutter and atrial fibrillation may occur in patients with prior surgical mitral valve (MV) repair or replacement and can be challenging for percutaneous catheter ablation. This study sought to determine the feasibility, acute success and durability of catheter ablation of atrial fibrillation or atrial tachycardia by way of a mitral isthmus line (MIL) or an anterior line (AL). Methods: A total of 81 patients (49 males, mean age 62±11 years) with prior MV replacement ( n = 30) or reconstruction ( n = 51) underwent creation of a MIL (34) and/or an AL (72). Results: Acute bidirectional block of the MIL was successfully achieved in 24/34 cases and of the AL in 64/72 patients. Patients of the control group without prior MV surgery were matched 1:1 with the valve group. In the AL control subgroup, acute bidirectional block was achieved in 65/72 patients. Acute blockage in the MIL control subgroup could be achieved in 31/34 patients. The MIL valve subgroup showed the worst results in terms of durability, whereas a similar trend emerged in the control group and the AL valve subgroup (probability of failure in MIL valve subgroup 2.224 vs. MIL control subgroup 0.605 [Hazard Ratio (HR) = 0.27, 95% confidence interval (CI), 0.11–0.65), P = .004]; probability of failure in AL valve subgroup 0.844 vs. AL control subgroup 1.03 [HR = 1.22 (95% CI, 0.66–2.26), P = .523]). Conclusions: Percutaneous creation of MIL and AL is feasible and safe in patients with prior MV replacement/repair and associated with moderate acute and long‐term success rates to achieve bidirectional block.